Maintaining Community in the Information Age - Evans, Karen F. author. aut Link
VII, 202 p.
Keywords: By exploring the experiences of community activists and organizations working with information and communication technology (ICT) to build communities, this book offers a grounded and informed study of the role ICT plays in people's lives. The author emphasizes the importance of networks built around trust, shared spaces and local knowledge bases in the formation of significant relationships in contemporary Western societies and in doing so, questions many of the assumptions which inform the rhetorics of the information age.